Efficacy of Cognitive Behavioral Therapy Compared to Other Evidence-Based Mental Health Interventions in Children and Adolescents with Symptoms of Childhood Adversities: A Scoping Review - Adeyemo, Idowu. R.; Adeyoyin, Oluwatobi; Ukagwu, Chijindu. A.; Ibrahim-Ojoawo, Atinuke; Asiedu, Lydia. A. (Asian Journal of Advanced Research and Reports, 2025)
Aims: To assess the relative efficacy of Cognitive Behavioral Therapy (CBT) compared to other proven therapies in improving mental health for children and adolescents affected by childhood trauma. Methodology: As part of the scoping review, a structured literature search of PubMed, Medline (EBSCO), PsychAPA, CINAHL, and Google Scholar identified studies published from January 1, 2022, to December 31, 2024, on evidence-based mental health interventions for minors experiencing trauma. English-language studies on cognitive behavioral therapy (CBT) or related interventions, either standalone or integrated, were included. Duplicates were removed, and references were reviewed for completeness. Data extracted included author, year, intervention type, therapy level, age group, and summarized findings. Eligible publication types were research articles, peer-reviewed articles, and systematically curated reviews. Results: The review synthesized findings from 26 studies published between 2022 and 2024, concentrating on therapeutic interventions for children and adolescents who have experienced adverse childhood experiences (ACEs). Trauma-focused cognitive behavioral therapy (TF-CBT) was identified as the most efficacious intervention, demonstrating robust effectiveness in alleviating symptoms of PTSD, anxiety, and depression across a range of clinical settings. The reviewed studies utilized diverse methodological approaches and predominantly focused on PTSD, anxiety, and depressive disorders, with a subset addressing substance use disorders, bereavement, and interpersonal functioning. Notably, the review highlighted significant gaps in the literature regarding the exploration of broader psychological outcomes and the efficacy of interventions beyond TF-CBT. Conclusion: Trauma-focused cognitive behavioral therapy (TF-CBT) stands out as the most effective treatment for enhancing mental health in children and adolescents experiencing trauma-related symptoms. Modifications of CBT and combined approaches, such as psychoeducation and family-oriented strategies, also play a significant role in diminishing post-traumatic stress symptoms and boosting resilience.